Development of self-efficacy skills of prospective music teachers in singing activity: insights of educators - Bi, Guanhua; Rauduvaitė, Asta (Frontiers in Psychology, 2025)
This study explores how self-efficacy is developed and expressed in prospective music teachers through singing-related coursework in Chinese higher education. Using a qualitative research design, data were collected through semi-structured interviews with eight university music educators who had experience teaching solfeggio, vocal music, choir, and Chinese opera. Qualitative content analysis revealed that self-efficacy in prospective music teachers is closely related to confidence, emotional regulation, collaboration, adaptability, and other essential skills for professional growth. Educators highlighted the importance of designing manageable singing tasks, encouraging peer observation, providing targeted feedback, and fostering a supportive and emotionally safe learning environment. The findings suggest that by systematically integrating self-efficacy enhancement strategies into music education curricula, educators can promote the holistic development of prospective music teachers. These insights contribute to practical implications for curriculum design, teacher preparation, and the ongoing advancement of music education in the context of contemporary challenges.